Research on Image Recognition Based on Improved YOLOv5s Network Model Algorithm - Xie, Keying; Li, Haoyuan; Chen, Xiaodan; Zheng, Weichao; Gan, Jing; Chen, Xinxin (2024 4th International Conference on Neural Networks, Information and Communication (NNICE), 2024)
In order to achieve rapid classification and extraction of pig target features. Propose an improved pig image object detection method based on YOLOv5s, using YOLOv5s adaptive anchor box calculation to obtain anchor boxes suitable for self built datasets; Combining convolutional block attention module to extract feature backbone network, improving model detection performance and reducing parameters. The Mosaic data augmentation method was used to enhance the image richness of the dataset and enhance the feature fusion ability of the network model. The improved algorithm was compared with the original YOLOv5s algorithm on a self-made dataset for ablation experiments. The results showed that the mean mAP of the improved algorithm reached 0.952, which showed a significant improvement in detection accuracy compared to other mainstream algorithms.